Quantifying habitat use of migratory fish across riverscapes using space‐time isotope models. Issue 7 (20th May 2019) - Brennan, Sean R.; Cline, Timothy J.; Schindler, Daniel E.
Abstract: Migratory animals pose difficult challenges to conservation and management because identifying critical habitats used throughout their lives is rarely possible. Endogenous tracers (e.g. isotope ratios) recorded in sequentially growing biogenic tissues, however, represent a potential source of unique insights at the more elusive temporal and spatial scales central to understanding the ecology of mobile species. To this end, a general probabilistic framework has emerged that quantitatively compares predictive models of isotopic variation across landscapes (called isoscapes) to the isotopic composition recorded in a biological tissue to determine the provenance and movements of animals throughout their lives. Although this spatially continuous approach to isotope‐based geographic assignment is becoming more common across taxa and ecosystems, adopting this framework to take advantage of serial isotope records stored within sequentially growing biogenic tissues (e.g. teeth or otoliths) is less common. Here, we construct a novel space‐time isotope model of provenance (STIMP) that determines the habitat use through time of migratory fish across river basins. To do so, this model integrates: strontium isotope ( 87 Sr/ 86 Sr) ratios across a riverscape, the serial records of 87 Sr/ 86 Sr within otoliths, habitat geomorphology and the directional movement patterns of fish through river networks. To illustrate an application of the model, we applied it to a published dataset from Chinook salmon ( Oncorhynchus tshawytscha ) harvested in 2011 during a coastal fishery in Bristol Bay, Alaska, U.S.A. Using this model, we show how individuals exploit an array of habitat types to achieve their juvenile growth prior to ocean migration, and that the intensity of habitat use among habitat types across the basin shifts spatially over the course of freshwater residence (e.g. from headwaters to migration corridors). The STIMP presented here integrates diverse information sources to reveal the cryptic juvenile movement patterns of a highly migratory species, providing new insights critical to their conservation. This general framework is applicable to any migratory taxa that use isotopically heterogeneous landscapes during their lives and record such variation in sequentially growing biogenic tissues.